2009
DOI: 10.1111/j.1537-2995.2008.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

From mad cows to sensible blood transfusion: the risk of prion transmission by labile blood components in the United Kingdom and in France

Abstract: Transfusion transmission of the prion, the agent of variant Creutzfeldt-Jakob disease (vCJD), is now established. Subjects infected through food may transmit the disease through blood donations. The two nations most affected to date by this threat are the United Kingdom (UK) and France. The first transfusion cases have been observed in the UK over the past 5 years. In France, a few individuals who developed vCJD had a history of blood donation, leading to a risk of transmission to recipients, some of whom coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 97 publications
(99 reference statements)
0
41
1
5
Order By: Relevance
“…Our studies here support the view that the level of prion infectivity in blood from prion-diseased individuals may be underestimated when assessed by intracerebral inoculation of rodents in comparison with bioassay of similar material in other experimental systems. This is particularly pertinent to our assessment here of prion-infected plasma that could be diluted by several orders of magnitude and still trigger a phenotypic response in the PrP transgenic Drosophila, but appears to contain a low level of infectivity when assayed in other systems [10,[15][16][17][18][19][20][21]. One possibility for the efficient detection of scrapie-infected sheep plasma by PrP transgenic Drosophila is that this invertebrate host does not normally express PrP and may therefore not have evolved suitable defence mechanisms that efficiently remove or sequester misfolded neurotoxic forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our studies here support the view that the level of prion infectivity in blood from prion-diseased individuals may be underestimated when assessed by intracerebral inoculation of rodents in comparison with bioassay of similar material in other experimental systems. This is particularly pertinent to our assessment here of prion-infected plasma that could be diluted by several orders of magnitude and still trigger a phenotypic response in the PrP transgenic Drosophila, but appears to contain a low level of infectivity when assayed in other systems [10,[15][16][17][18][19][20][21]. One possibility for the efficient detection of scrapie-infected sheep plasma by PrP transgenic Drosophila is that this invertebrate host does not normally express PrP and may therefore not have evolved suitable defence mechanisms that efficiently remove or sequester misfolded neurotoxic forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies revealed that prion infectivity titres of blood samples harvested during the asymptomatic phase of prion disease were up to 10-fold less than those collected during the clinical phase [10,19,20,22]. Infectious prions were found to be associated with white and red blood cells, platelets and plasma, although interspecies variations existed with regard to the distribution of prion infectivity in these different blood fractions [10,[15][16][17][18][19][20][21]. Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…37,38 Depending on the titer of transmitted PrP Sc , the detection of preclinical scrapie in recipient lambs may take anywhere from between 594 days and 1,089 days posttransmission. CWD infectivity in white-tailed deer was not found in platelet-poor plasma but in the platelets, whereas infectivity was observed in the plasma of sheep, hamsters, and humans.…”
mentioning
confidence: 99%